Perspectivas de democratização da gestão educacional e escolar em Quevedos/RS - Moraes, Marília do Nascimento (2022)
This work is part of a master's research, linked to the MPS (Master of Professional Studies) in Public Policy and Educational Management at the Universidade Federal de Santa Maria (Federal University of Santa Maria in Rio Grande do Sul State, Brazil). In addition, it integrates the studies of the Gestar/CNPq Research Group on Public Policy and Educational Management linked to The National Council for Scientific and Technological Development (CNPq). Its general objective is to understand, from the perspective of democratization processes in Quevedos/RS Municipal Education System, which factors and parameters are related to educational and school management. It consists of a research with a qualitative approach, of the case study type. Document analysis of national and municipal legislation as well as semi-structured interviews with the Secretary and the Supervisor of the Municipal Education Secretariat, School Managers and a Municipal Counselor of Education have been used for the construction of data. It was also applied an online questionnaire with teachers working in municipal schools. Data processing and interpretation were based on content analysis. As a theoretical reference, authors such as Bordignon (2009), Lück (2006); Paro (2007), Gadotti (2000), among other bibliographies have been used. Research conclusions: all evidences suggest that there is still resistance regarding the effectiveness of the principles of education´s democratization at the municipal level. Especially when it comes to the effective implementation of participation mechanisms, such as: the existence of School Councils and their role in decision-making and power sharing; the choice of school administration by the communities; the existence of municipal legislation to regulate the processes of education´s democratization; the financial autonomy of schools and the Municipal Education Council; a political-pedagogical project created and tailored by the school communities, among others. In the studied context, it has been observed that the Municipal Education System (MES) was created in 2021 and, in this sense, it is important to invest in strategies towards power decentralization; administrative, pedagogical, and financial autonomy; the participation of school communities, as well as in the role of the Municipal Education Council as a normative body for the MES. That being said, an educational product was developed, consisting of a booklet comprising "Parameters for the democratization of educational and school management in Quevedos/RS", in an attempt to contribute to the reflection and qualification of the educational management processes in this municipality from the democratization´s perspective.